Schleiermacher : Christmas dialogue, the Second speech, and other selections - Schleiermacher, Friedrich, 1768-1834 (Classics of Western spirituality, 2014)
Friedrich Daniel Ernst Schleiermacher (1768-1834), the "father of modern theology". was religiously formed in the Pietist tradition and always remained a deeply spiritual person. His spirituality pervades all his work, including his earlier Romantic works, his sermons and letters, and even his magnum opus, The Christian Faith. This volume, prepared by a leading Schleiermacher scholar, makes a vital contribution to the history of spirituality and to Schleiermacher studies by presenting, along with an introduction and biographical sketch, fresh translations of selected works that demonstrate the many aspects of his spirituality and how they permeate his religious thought. (Back cover).